A Graftable Quaternary Ammonium Biocidal Polymer Reduces Biofilm Formation and Ensures Biocompatibility of Medical Devices. Issue 5 (14th January 2021) - Bouloussa, Houssam; Saleh‐Mghir, Azzam; Valotteau, Claire; Cherifi, Chahrazad; Hafsia, Narjes; Cohen‐Solal, Martine; Court, Charles; Crémieux, Anne‐Claude; Humblot, Vincent
Abstract: A quaternized polyvinylpyridine (Q‐PVP) polymer methanolic solution synthesized in a single step is used to covalently graft titanium surfaces. Q‐PVP is quaternized with varying N + /N ratios. 1 cm 2 pure titanium plates are polished and activated. Treated samples are grafted by spin coating or dip‐coating (grafting‐to method). Surfaces are characterized by X‐ray photoelectron spectroscopy, polarization modulation reflection absorption IR spectroscopy, atomic force microscopy, scanning electron microscopy, and surface charge density calculation. Polymer leaching is assessed at 7 days. Biocompatibility is assessed on MC3T3 and L929 cells (MTT‐assay) and SEM. In vitro antibacterial activity is assessed on methicillin‐resistant Staphylococcus aureus (MRSA) at 1 and 24 h (37 °C in brain heart infusion) and at 7 days in a biofilm model. Polymers exceeding 31.3 ± 0.7% quaternization led to bactericidal surfaces. Bactericidal activity increased with surface cationic density. Surface cationic density and biocompatibility are inversely correlated. Polymers with 44.6 ± 1.2% quaternization are antibacterial and biocompatible. High‐density Q‐PVP inhibited MRSA biofilm formation. Q‐PVP is a promising candidate for antibacterial surface modification. Further in vivo studies are required. Abstract : Surface modification of pure titanium with silanized and partially quaternized polyvinylpyridine represents a good compromise of biocompatibility and bactericidal activity against methicillin‐resistant Staphylococcus aureus . Surface characterization, in vitro bacteriological data, and in vitro cell‐viability data are detailed. If confirmed in vivo, this covalently grafted polymer may be a good candidate to prevent biofilm formation on medical devices.